Immune responses in retinal gene therapy: challenges, mechanisms, and future strategies - Ma, Yawei; Shen, Yin (Frontiers in Immunology, 2025)
Retinal gene therapy has advanced significantly, offering potential treatments for inherited retinal diseases (IRDs) such as retinitis pigmentosa, which previously lacked effective interventions. Central to this progress are adeno-associated virus (AAV)-based delivery systems, which have become the primary platform for ocular gene therapy due to their favorable safety profile, ability to target specific retinal cell types, and long-lasting therapeutic effects. However, accumulating evidence reveals that even “immune-privileged” retinal microenvironments are not exempt from immune challenges, affecting both the safety and efficacy of these therapies. Both innate immune pathways and adaptive responses can induce intraocular inflammation, leading to reduced transgene expression and compromised treatment. Understanding how these immune mechanisms interact with therapeutic outcomes is crucial for developing effective intervention strategies. This review examines evidence from both animal models and human trials to explore how immune activation affects treatment efficacy across various delivery methods and vector designs. We also assess emerging strategies aimed at protecting retinal function while reducing systemic toxicity.